This valley of perpetual dream : a close commentary on Shelley's The triumph of life : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Simonsen, Pauline Margaret (Massey University, 1989)
The Triumph of Life" is a cryptic final work for Shelley to leave to posterity. It is both unlike and yet like his previous work. It is unlike in that it addresses itself to the non-ideal, to a cruel and devastating present existence.¹ Perhaps only The Cenci approaches the same degree of disillusionment. It is like in that it displays that "tough-minded" Shelleyan scepticism that C. E. Pulos has elucidated so well.² C. E. Pulos, The Deep Truth: A Study of Shelley's Scepticism (Lincoln: University of Nebraska Press, 1954). The Shelley who wrote the final line of "Mont Blanc", who included the famous last speech of Demogorgon in Prometheus Unbound, is in this poem given full rein. The debate still rages as to whether he allows any idealism into "The Triumph of Life" at all. This closely structured poem, full of gripping images that remain with one long after the poem has been read, is Shelley at his best. In it, the poet who wrote the "Ode to the West Wind" brings his deep concern with the nature of life to fruition. The issues that emerge from an analysis of the text reflect this concern with the fundamentals of existence. For this reason, I believe it to be - despite its fragmentary nature - a great document on modern life. [From Foreword]
Keywords: Shelley, Percy Bysshe 1792-1822; Criticism interpretation